Aesthetic perceptions and social judgments about different enamel opacities - Fernanda Mafei Felix da SILVA; Marcela Baraúna MAGNO; Aline Borburema NEVES; Raildo da Silva COQUEIRO; Marcelo de Castro COSTA; Lucianne Cople MAIA; Matheus Melo PITHON
Abstract This study aimed to evaluate adolescents' aesthetic perceptions and their social judgments regarding different enamel opacities. Sample size was calculated and resulted in the inclusion of 100 adolescents (aged 10 to 15 years) from a public school in Jequié, Bahia, Brazil. Images of enamel opacities were manipulated to create aesthetic enamel defects, such as enamel color changes (unilateral and bilateral white opacity, unilateral and bilateral yellowish opacity, and unilateral and bilateral yellowish opacity with loss of structure). The images of the opacities were based on Fédération Dentaire Internationale's Developmental Defects of Enamel (DDE) Index. Aesthetic perception and social judgments were evaluated using a validated questionnaire with 12 questions (six positive and six negative points) on social aspects, considering the six manipulated images and the control. The photographic analyses were projected one-by-one by computer to adolescents individually in a classroom. Participants had one minute to observe each image and answer the questionnaire. The data were analyzed by descriptions, and the Friedman Wilcoxon test (p < 0.05). The results indicate that all opacities negatively impacted social judgment (p < 0.001). The enamel aesthetic defects most affecting an individual's perception were bilateral yellow opacity with or without loss of structure (p < 0.001). Regarding social judgment, all participants showed a negative perception of all the tested opacity types (p < 0.001). In conclusion, even opacities presenting only a color change caused aesthetic dissatisfaction to the individuals and changes in their social judgment toward others. Color changes in dental enamel have several aesthetic consequences.